Analisis Perilaku Konsumtif Penggemar K-POP (Kpopers) dalam Perspektif Hadis Tasyabbuh - Najma Zahiroh; Nasrulloh (Al-Kindi, 2026)
This study aims to analyze the consumer behavior of Muslim K-Pop fans (Kpopers) from the perspective of the hadith on tasyabbuh, while also providing education on the legal boundaries of entertainment in Islam. Using a qualitative method with a descriptive analysis approach, data were collected through a digital open-ended questionnaire administered to 13 Muslim student respondents aged 20–23. The results indicate that the majority of informants exhibit consumption behavior driven by internal motivations for emotional satisfaction as well as external influences from fandom culture, particularly in the purchase of photocard, albums, and attending concerts. From the perspective of the hadith on tasyabbuh, these consumption activities and the K-pop fans’ enthusiasm are deemed to remain within reasonable limits and are permissible in Islam because they are purely matters of muamalah and worldly entertainment, not part of non-Muslim religious rituals or practices. Nevertheless, fan characteristics can be divided into two types: wise fans who are able to control their spending based on the priority of urgent needs, and impulsive fans who are prone to falling into wastefulness (israf) due to a lack of self-control. Therefore, self-control remains necessary so that this enjoyment of entertainment does not violate religious law.